A mathematical model of the oar blade - water interaction in rowing - Caplan, N.; Gardner, T. (Journal of Sports Sciences, 2006)
Our aim was to present a mathematical model of rowing and sculling that allowed for a comparison of oar blade designs. The relative movement between the oar blades and water during the drive phase of the stroke was modelled, and the lift and drag forces generated by this complex interaction were determined. The model was driven by the oar shaft angular velocity about the oarlock in the horizontal plane, and was shown to be valid against measured on-water mean steady-state shell velocity for both a heavyweight men's eight and a lightweight men's single scull. Measured lift and drag force coefficients previously presented by the authors were used as inputs to the model, which allowed for the influence of oar blade design on rowing performance to be determined. The commonly used Big Blade, which is curved, and it's flat equivalent were compared, and blade curvature was shown to generate a 1.14% improvement in mean boat velocity, or a 17.1 m lead over 1500 m. With races being won and lost by much smaller margins than this, blade curvature would appear to play a significant role in propulsion.